飞艇平台推力矢量转向系统的设计 - 彭桂林; 吴晴 (Jixie chuandong)
Aerocraft which is lighter than air is applied to hovering flight and vertical taking off and landing by thrust vector steering mechanism.According to the analysis of principle of thrust vector steering mechanism,a new structural project is deseribed,which is from the transmission of worm-wheel steering,and exact adjustment of redirector.After the target parameters are ensured,selection basis of servo motor is given by the calculation of moment,and then design of the worm-wheel steering is carried out.Lastly,the isochronous steering of two airscrews is realized.Apparently,the study has reference value for the design of power control in airship platform.